IDENTIFIKASI PEMANFAATAN JENIS TUMBUHAN OBAT DI KAWASAN CAGAR ALAM KAKENAUWE DESA KAKENAUWE KECAMATAN LASALIMU KABUPATEN BUTON: IDENTIFIKASI PEMANFAATAN JENIS TUMBUHAN OBAT DI KAWASAN CAGAR ALAM KAKENAUWE DESA KAKENAUWE KECAMATAN LASALIMU KABUPATEN BUTON - La Ode Agus Salim Mando; Ryan Fadly Paripurna; Agus Setiawan; Niken Pujirahayu; Abigael Kabe; Mariana Zainun (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
Abstract: Medicinal plants are plants that are used to reduce, eliminate or cure certain diseases through traditional treatment. This research was carried out from July to August 2024. This research aims to identify types of medicinal plants around the Kakenauwe Nature Reserve Area and find out how medicinal plants are used by the people of Kakenauwe Village. This research uses a purposive sampling method with data collection techniques through observation, interviews and literature study. The research data were analyzed descriptively and presented in the form of descriptions and tables. The results of the research identified 24 types of medicinal plant species belonging to 22 families with the Asteraceae family being the most widely used by the people of Kakenauwe Village and most of their habitus consisting of 5 types of trees, 1 type of shrub, 4 types of lianas, 3 types of shrubs, 3 types of epiphytes. , and 8 types of herbs and plant parts are more widely used, namely leaves and different ways of processing plants in terms of healing, namely applying topically, drinking or boiling, dripping and chewing. Keywords: Application, Kakenauwe Nature Reserve, Medicinal Plants